2009
DOI: 10.1002/j.2055-2335.2009.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Transgressions by Australian Pharmacists

Abstract: Background Investigating professional transgressions by pharmacists will aid to minimise their occurrence and ensure that the public's trust and well‐being are not compromised Aim To compare the definition of professional transgression in all Australian pharmacy acts; to identify the characteristics of pharmacists most likely to transgress; to identify the most prevalent transgressions; and to identify the justification provided by pharmacists for committing transgression. Method Definitions of professional tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Four studies used qualitative interview or focus group techniques [42,48,49,60]. Six studies (one reported in two papers) used retrospective reviews of disciplinary/performance records to explore performance [38][39][40]61,62,68,71]. Three studies used retrospective analysis of error data [52,53,72], whilst seven studies used prospective data collection techniques on errors [37,42,56,69,70] or clinical interventions [50,64].…”
Section: Research Methods Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies used qualitative interview or focus group techniques [42,48,49,60]. Six studies (one reported in two papers) used retrospective reviews of disciplinary/performance records to explore performance [38][39][40]61,62,68,71]. Three studies used retrospective analysis of error data [52,53,72], whilst seven studies used prospective data collection techniques on errors [37,42,56,69,70] or clinical interventions [50,64].…”
Section: Research Methods Usedmentioning
confidence: 99%
“…Two studies were conducted in Canada [38][39][40], two in Australia [62,63] and two in Europe [57,67]. One study was a literature review reporting data from a number of countries [51].…”
Section: Country Of Publicationmentioning
confidence: 99%
“…This may partially explain why hospital pharmacists seem to be less involved in ethical transgressions than those activating in community settings (in Australia, 1.6% of the pharmacists sanctioned for violations of professional ethics were working in hospitals and 97% in community settings) [26].…”
Section: The Clash Of Economics and Ethicsmentioning
confidence: 99%
“…Sometimes business difficulties in pharmacy lead to fraud, as illustrated by an Australian pharmacist sanctioned by the professional body for violating professional rules in the attempt to repay business debts [26]. Any violation of the legal rules is inherently unethical, but actions and behaviours satisfying the minimal legal requirements are not necessarily ethical; the "ethical" label is to be applied to behaviours that go "above and beyond" the regulatory framework in force [5].…”
Section: How Economics May Trump Ethics In Daily Pharmacy Lifementioning
confidence: 99%
See 1 more Smart Citation